2012
DOI: 10.1161/circheartfailure.111.963991
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in Advanced Heart Failure Patients With Left Ventricular Assist Devices for Destination Therapy

Abstract: Background— The HeartMate II (HMII) destination therapy (DT) trial demonstrated significant improvements in outcomes in continuous-flow left ventricular assist devices compared with patients implanted with the pulsatile-flow HeartMate XVE. The primary hypothesis of the current study is that trial patients enrolled after the initial data cohort would have better clinical outcomes. Methods and Results— Two hundred eighty-one patients who un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
169
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(177 citation statements)
references
References 21 publications
3
169
0
4
Order By: Relevance
“…8 Initial clinical trials of older pulsatile flow LVADs used as destination therapy demonstrated 1-year survival of 52%, 9 and more recent studies of continuous flow pumps, used for the same indication, showed 1-year survival of 73%. 10 These studies also documented improvements in functionality and quality of life relative to that seen with medicallytreated HF. With the observed gains in longevity, functionality, and quality of life in destination VAD recipients, mechanical circulatory support compares favorably with heart transplantation, the only long-term solution for patients with end-stage HF just a decade ago.…”
mentioning
confidence: 93%
“…8 Initial clinical trials of older pulsatile flow LVADs used as destination therapy demonstrated 1-year survival of 52%, 9 and more recent studies of continuous flow pumps, used for the same indication, showed 1-year survival of 73%. 10 These studies also documented improvements in functionality and quality of life relative to that seen with medicallytreated HF. With the observed gains in longevity, functionality, and quality of life in destination VAD recipients, mechanical circulatory support compares favorably with heart transplantation, the only long-term solution for patients with end-stage HF just a decade ago.…”
mentioning
confidence: 93%
“…20 In regards to long-term LVAD support, the HMII DT trial reported 2-year survival rates increasing from 58% to 63% in the current era. 21 We report lower mortality at our centre, potentially attributable to our rigorous patient selection process and interprofessional LVAD education. Notably, our results implicated the index admission as the highest-risk time period for LVAD mortality, implicating patient selection as a major contributor.…”
Section: Discussionmentioning
confidence: 73%
“…10,[16][17][18][19]21 The limited literature examining postoperative LOS in the LVAD population varies widely, ranging from 17 days to 25 days. 16,18 Compared with other centres, our centre leans toward having increased length of postoperative stays.…”
Section: Discussionmentioning
confidence: 99%
“…In the best-case scenario, it results in an appreciable improvement in quality of life until transplantation, with significant recovery thereafter. 3,[10][11][12][13][14] However, realization of this outcome rests on many contingencies and inevitably involves burdens. 9,15 It is important to recognize that consequences must be evaluated based on the values of the individuals affected.…”
Section: Commentarymentioning
confidence: 99%